Ethnicity and COVID-19 outcomes among healthcare workers in the UK: UK-REACH ethico-legal research, qualitative research on healthcare workers’ experiences and stakeholder engagement protocol - Kamlesh Khunti; Katherine Woolf; Manish Pareek; Fatimah Wobi; Amit Gupta; Catherine Johns; Sue Carr; Chris McManus; Laura Gray; David Ford; Keith Abrams; Anna Guyatt; et al. (BMJ Open)
Introduction As the world continues to grapple with the COVID-19 pandemic, emerging evidence suggests that individuals from ethnic minority backgrounds may be disproportionately affected. The United Kingdom Research study into Ethnicity And COVID-19 outcomes in Healthcare workers (UK-REACH) project has been initiated to generate rapid evidence on whether and why ethnicity affects COVID-19 diagnosis and clinical outcomes in healthcare workers (HCWs) in the UK, through five interlinked work packages/work streams, three of which form the basis of this protocol. The ethico-legal work (Work Package 3) aims to understand and address legal, ethical and acceptability issues around big data research; the HCWs experiences study (Work Package 4) explores their work and personal experiences, perceptions of risk, support and coping mechanisms; the stakeholder engagement work (Work Package 5) aims to provide feedback and support with the formulation and dissemination of the project recommendations.Methods and analysis Work Package 3 has two different research strands: (A) desk-based doctrinal research; and (B) empirical qualitative research with key opinion leaders. For the empirical research, in-depth interviews will be conducted digitally and recorded with participants permission. Recordings will be transcribed, coded and analysed using thematic analysis. In Work Package 4, online in-depth interviews and focus groups will be conducted with approximately 150 HCWs, from across the UK, and these will be recorded with participants consent. The recordings will be transcribed and coded and data will be analysed using thematic analysis. Work Package 5 will achieve its objectives through regular group meetings and in-group discussions.Ethics and dissemination Ethical approval has been received from the London-Brighton & Sussex Research Ethics Committee of the Health Research Authority (Ref No 20/HRA/4718). Results of the study will be published in open-access journals, and disseminated through conference presentations, project website, stakeholder organisations, media and scientific advisory groups.Trial registration number ISRCTN11811602.